The effectiveness of anti-adhesive barrier based on carboxymethylcellulose 5 mg and sodium hyaluronate 2.5 mg in various methods of surgical treatment of ectopic tubal pregnancy - Larisa E Fitisheva; Vadim G Mozes; Igor S Zaharov; Kira B Mozes (IP Berlin A.V., 2019)
Aim. To evaluate the effectiveness of the anti-adhesive barrier in the form of a gel based on carboxymethylcellulose 5 mg and sodium hyaluronate 2.5 mg with various techniques of surgical treatment of ectopic tubal pregnancy. Materials and methods. A randomized study was conducted on 98 women who underwent laparoscopic resection of the ampulla of the fallopian tube, together with a embryo, followed by neostomatoplasty or salpingostomy with or without an anti-adhesive barrier. The primary outcome of the study was the incidence of uterine pregnancy and its outcomes at 18 months of follow-up; secondary outcomes were the frequency of adhesions in the pelvis, the frequency of patency of the operated fallopian tube according to second look laparoscopy with chromohydrotubation by 3 months of follow-up. Results. At 3 months of follow-up, the use of an anti-adhesion barrier reduced the incidence of postoperative adhesions in the area of the operated fallopian tube and the degree of adhesions in the pelvis; increased the frequency of patency of the operated fallopian tube when performing laparoscopic resection of a portion of the ampulla of the fallopian tube, followed by neostomatoplasty. By the 18th month of observation, no statistically significant difference in the incidence of spontaneous pregnancy and its outcomes in the studied women was detected. Conclusion. Use of 5 mg carboxymethylcellulose and 2.5 mg sodium hyaluronate anti-adhesive barrier with various organ-preserving methods of surgical treatment of ectopic tubal pregnancy reduces the frequency and extent of postoperative adhesions in the area of the operated fallopian tube, in the small pelvis, but does not increase fertility in the postoperative period.